The Concept Of Licensing Authority Of The Architectural Work Modification Of Cultural Heritage Buildings - M.G. Endang Sumiarni; Yustina Niken Sharaningtyas; Sefriani; Y. Sri Pudyatmoko (Prophetic Law Review, 2022)
This research aims to identify the licensing authority over architectural works and modification of designated Cultural Heritages. In addition, this research examines the antinomy of legal concepts, including the antinomy of the legal concept of a licensing authority, the antinomy of the legal concept of modification of creation, and the antinomy of the legal concept of cultural heritage. With normative research, this study reveals that there is no legal certainty, between the local and central government, concerning licensing authority to cultural heritage building adaptation. There is no such a unitary system or firm and clear SOPs, which has resulted in the demolition and destruction of cultural heritage buildings. There are differences of opinion regarding the authority to permit the alteration of architectural works of cultural heritage buildings that have been stipulated. Permits for the restoration of cultural heritage buildings are obtained not through a building permit but through BPPM DIY (Licensing and Investment Service). These permits include restoration permits, adaptation permits, and development permits, especially for revitalization and utilization. There is no balance between moral and economic rights of the owner of the cultural heritage building. The preservation is more likely to emphasize moral rights but still overlooking the economic rights of the creator/owner.Keywords: licensing authority, architectural work, adaptation, cultural heritage building. Konsep Otoritas Perizinan Modifikasi Karya Arsitektur Bangunan Cagar Budaya AbstrakPenelitian ini bertujuan untuk mengidentifikasi kewenangan perizinan atas karya arsitektur dan modifikasi Cagar Budaya yang ditetapkan. Selain itu, penelitian ini mengkaji antinomi konsep hukum, antara lain antinomi konsep hukum otoritas perizinan, antinomi konsep hukum modifikasi ciptaan, dan antinomi konsep hukum warisan budaya. Dengan kajian normatif, kajian ini mengungkapkan bahwa belum ada kepastian hukum, antara pemerintah daerah dan pusat, mengenai kewenangan perizinan terhadap adaptasi bangunan cagar budaya. Tidak ada sistem kesatuan atau SOP yang tegas dan jelas sehingga mengakibatkan pembongkaran dan perusakan bangunan cagar budaya. Terdapat perbedaan pendapat mengenai kewenangan izin perubahan karya arsitektur bangunan cagar budaya yang telah ditetapkan. Izin pemugaran bangunan cagar budaya diperoleh bukan melalui izin mendirikan bangunan melainkan melalui BPPM DIY (Dinas Perizinan dan Penanaman Modal). Izin tersebut meliputi izin restorasi, izin adaptasi, dan izin pembangunan, terutama untuk revitalisasi dan pemanfaatan. Tidak ada keseimbangan antara hak moral dan ekonomi pemilik bangunan cagar budaya. Pelestarian tersebut lebih cenderung mengedepankan hak moral namun tetap mengabaikan hak ekonomi pencipta/pemilik.Kata Kunci: perizinan, karya arsitektur, adaptasi, bangunan cagar budaya.